1954
DOI: 10.1115/1.4015020
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Effects of Cyclic Thermal Stresses on a Ductile Metal

Abstract: The results of a study of cyclic strain and fatigue failure arising from cyclic thermal stresses are reported. By means of a test apparatus described in a companion paper, a cyclic temperature is imposed on a thin tubular test specimen subjected to complete longitudinal constraint. Hence, the cyclic strain is the independent variable. The following studies are reported: (a) Effect of thermal-stress cycling on strain hardening and life-to-failure for a fixed mean temperature, (b) effect of degree and kind of pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
201
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,015 publications
(205 citation statements)
references
References 0 publications
3
201
0
1
Order By: Relevance
“…Most models are based on a physical dimension, like a certain stress or strain state, or an absorbed energy equivalent, 37 or on mathematical models, which introduce lifetime influencing parameters. A common lifetime approach is the strain-based Manson-Coffin/Basquin approach (Equation 1), which consists of the Basquin 38 and Manson-Coffin [39][40][41] equations.…”
Section: Multiaxial Fatigue Lifetime Descriptionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most models are based on a physical dimension, like a certain stress or strain state, or an absorbed energy equivalent, 37 or on mathematical models, which introduce lifetime influencing parameters. A common lifetime approach is the strain-based Manson-Coffin/Basquin approach (Equation 1), which consists of the Basquin 38 and Manson-Coffin [39][40][41] equations.…”
Section: Multiaxial Fatigue Lifetime Descriptionsmentioning
confidence: 99%
“…Most models are based on a physical dimension, like a certain stress or strain state, or an absorbed energy equivalent, 37 or on mathematical models, which introduce lifetime influencing parameters. A common lifetime approach is the strain‐based Manson‐Coffin/Basquin approach (Equation 1), which consists of the Basquin 38 and Manson‐Coffin 39–41 equations. ϵagoodbreak=ϵa,italicelgoodbreak+ϵa,italicplgoodbreak=σfE2Nfbgoodbreak+ϵf2Nfc This approach includes the total strain amplitude ϵa, the elastic strain amplitude ϵa,italicel, the plastic strain amplitude ϵa,italicpl, the total number of cycles to failure Nf, and Young's modulus E.…”
Section: Multiaxial Fatigue Lifetime Descriptionsmentioning
confidence: 99%
“…Among them, the SWT model is proposed by Smith et al, 53 and the SWT parameter extended by Socie 54 has been widely used, which is found to be suitable for aluminum alloys 55 . The expression of life model is shown below: σmaxnormalΔεn2goodbreak=σf2E2Nf2bgoodbreak+σfεf2Nfb+c, where σmax is the maximum normal stress on the critical plane, normalΔεn2 is the positive strain amplitude on the critical plane, E is the modulus of elasticity, and σf, εf, b , and c are material parameters in Coffin–Manson equation, 56,57 which are calculated by using the estimation formulas 58 . And the four calculated parameters are 910 MPa, −0.095, −0.69, and 0.35, respectively.…”
Section: Two Examples Based On the Clipping Methodsmentioning
confidence: 99%
“…The Coffin-Manson equation used in the strength calculations defines the dependence of durability under loading with controlled strain (e k = constant) on the cyclic plastic strain e 0 [35,36]:…”
Section: Statistical Assessment Of Low-cycle Fatigue Curvesmentioning
confidence: 99%